The Impact of Land Use Changes on The Service Life of Wlingi Reservoir - Indang Dewi Rarasati; Suripin Suripin; Dyah Ari Wulandari; Dwiva Anbiya Taruna (Green Publisher Indonesia, 2025)
One of the factors that can affect changes in the capacity of a reservoir is the amount of sedimentation that settles at the bottom of the reservoir. Several reservoirs in Indonesia have experienced shallowing due to sedimentation. The increase in sedimentation rate is caused by high land erosion. Land erosion comes from changes in land use in a River Basin Area. The benefits of the Wlingi Reservoir are as a flood controller of 2.37 m3/s, irrigation supply of 13,600 hectares, as a power plant that can drive the turbine of a PLTA unit with a power of 2 x 27 MW. In this study, land use data comes from ESRI satellite imagery, which differs from previous studies. This study aimed to obtain sediment yield from land use changes in the Brantas Hulu Watershed with Wlingi Reservoir outlet point from 2018 to 2023 and to predict remaining service life of the reservoir. The method used to calculate the erosion rate is USLE, which uses GIS (Geographic Information System) software. The results showed that undisturbed forests dominated land use, and land use changes for 6 years were volatile. The average sediment rate for 6 (six) years was 0.011 mm/year. The predicted service life is that Wlingi Reservoir can only serve for 91 years. These findings highlight the urgency of implementing effective sediment management strategies. Without intervention, sedimentation will reduce the reservoir's capacity to support irrigation and hydropower, impacting regional water management and food security and limiting flood mitigation capabilities in East Java.